The influence of European jurisprudence on national criminal law in the field of corruption - Carmen Lorena VLĂDUŢ (Analele Ştiinţifice ale Universităţii "Al.I. Cuza" din Iaşi. Ştiinţe Juridice)
The article analyzes the influence of European jurisprudence, especially that of the Court of Justice of the European Union (CJEU) on romanian criminal law in the field of corruption. The CJEU issued significant judgments that require the member states to harmonize the rules in the field of corruption and the application of effective and dissuasive sanctions for acts of corruption. Through notable cases such as „C 105/14 Taricco and others”, the CJEU emphasized the need for adequate national legislation in the fight against corruption. Instruments such as the European Arrest Warrant (EA) and the „ne bis in idem” principle have been strengthened by CJEU rulings, facilitating judicial cooperation and the protection of fundamental rights. However, the effective implementation of these European standards presents challenges, requiring continuous collaboration. The jurisprudence of the CJEU has a profound impact on national criminal law, contributing significantly to the fight against corruption within the European Union.